Kepemimpinan dalam Manajemen Mutu Pendidikan: Sebuah Kajian Literatur pada Model Transformasional, Visioner, dan Gaya Kepemimpinan - Azizatun Nisa; Nadiyatul Kholifah; Mu’alimin Mu’alimin (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
Leadership and quality management issues in education are important concerns in efforts to improve the quality of educational services and outcomes. Various studies have shown that the quality of principal leadership significantly influences the performance of educational organizations, but a comprehensive synthesis of leadership models and their implementation in quality management is still limited. This article aims to review the literature related to the role of leadership in implementing quality management strategies. The method used is a literature review with a qualitative approach. Data were obtained from Google Scholar and the Publish or Perish application with the keyword "Quality Leadership," covering the publication period 2020–2025. Of the 20 identified articles, a screening and selection process was carried out, resulting in 5 articles for in-depth analysis. The results of the thematic review indicate three main trends: (1) the integration of leadership and quality management strategies impacts educational performance and standards, (2) transformational, visionary, and leadership styles contribute differently to quality improvement, and (3) the urgency of effective leadership is seen in the ability to build a quality culture and face global challenges. The conclusion of this study emphasizes the central role of leadership in educational quality. Further research is recommended to explore the influence of digital and collaborative leadership in the context of 21st-century education.